2003
DOI: 10.1080/0014013021000048006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of label format on knowledge acquisition and perceived readability by younger and older adults

Abstract: This research examines consumers' information acquisition and preference for labels of a simulated over-the-counter (OTC) medication. Twelve otherwise identical OTC drug bottles were compared with different back labels varying in (a) print size, (b) amount of white space between text, and (c) label design (standard vs extended/pull-out). A no back label condition served as a control. Older (mean age=77.7 years) and younger (mean age=21 years) adults were given one of the 12 bottles and asked to perform one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…study, 38% of the interviewed patients had problems reading or understanding the patient information leaflets. Older consumers may be unable to acquire information in the 'fine' print frequently found in various kinds of product inserts 19. It is recommended that a suitable size should be chosen.…”
Section: Discussionmentioning
confidence: 99%
“…study, 38% of the interviewed patients had problems reading or understanding the patient information leaflets. Older consumers may be unable to acquire information in the 'fine' print frequently found in various kinds of product inserts 19. It is recommended that a suitable size should be chosen.…”
Section: Discussionmentioning
confidence: 99%
“…Besides this, the print size of label was also very small to read. Studies have shown an association between the print sizes and medication errors [ 27 , 28 ]. This might contribute to increased medication errors particularly by the elderly people.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies, patients preferred PWLs with increased label size and a bigger font size. [ 21 , 26 – 28 ] Also feedback related to design such as the use of color highlighting behind the words versus color highlighting behind the pictures show that it is important to also integrate information design while refining PWLs. [ 11 ] In the past, there has been a lot of focus on enhancing the comprehension of the written content of PWLs, and using pictures/icons to depict the instructions.…”
Section: Discussionmentioning
confidence: 99%